Clinical Manifestations of Aortocaval Fistulas in Ruptured Abdominal Aortic Aneurysm: Report of Two Cases - Emmanouil D. Psathas; Stella Lioudaki; Mikes Doulaptsis; Petros Charalampoudis; Chris Klonaris; Chris Verikokos (Case Reports in Surgery)
Aortocaval fistula (ACF) is an unusual complication of ruptured abdominal aortic aneurysm (AAA), involving less than 3–6% of all ruptured cases. The clinical presentation is often obscure, depending on the coexistence of retroperitoneal rupture and hemodynamic instability. Prompt preoperative diagnosis is essential in order to plan the operative approach and improve patient’s outcome. We report the surgical treatment of two patients presented in the emergency department with ACF due to ruptured AAA, each with different clinical presentation, emphasizing the high index of suspicion needed by the clinician to early diagnose and treat this often lethal condition. Operative strategy and special considerations in the management of this subgroup of patients are also discussed.